Existential reflection and morality - Sopcak, Paul; Kuiken, Don; Douglas, Shawn (Frontiers in Communication, 2022)
This paper presents a series of three studies describing how reading literature promotes empathy and moral outcomes. We add three contrasts to this field of empirical study: (a) an explanatory and interpretative form of narrative reading engagement (Integrative Comprehension) is contrasted with an expressive and explicative form of aesthetic reading engagement (Expressive Enactment); (b) an explanatory and interpretive form of cognitive perspective-taking (a component of Integrative Comprehension) is distinguished from an expressive and explicative form of empathy (a component of Expressive Enactment); and (c) a local form of moral outcome (involving changes in attitude toward a specific group or outgroup) is distinguished from a global form of moral outcome (involving an inclusive respect for human subjectivity). These contrasts are clarified and contextualized within existential-phenomenological discussions of sense-giving lived experience, agency, and morality. In conclusion, we offer a framework that specifies the potential impact on wellbeing of a form of literary reading that involves existential reflection, especially as conceived within the emerging field of existential positive psychology.